The Optimal Mix Between Funded and Unfunded Pensions System When People Care About Relative Consumption - Markus Knell (Oesterreichische Nationalbank (OeNB), 2008)
In this paper I derive the optimal portfolio mix between a funded and an unfunded pension system when people care about their consumption relative to a reference group. Pay-as-you-go systems with fixed contribution rates have the property that pension benefits are tied to labor income. This lowers the uncertainty of individuals'future relative position and thus increases the attractiveness of unfunded systems. The paper shows analytically that in an OLG model the optimal share of funding decreases with the strength of individuals' concern for relative standing. A calibrated version of the model that uses data for various countries and time periods suggests that the sensitivity of the optimal share of funding to the concern of relative standing is also quantitatively important. For reasonable assumptions about reference standards it is typically around 20%.
Keywords: H55; G11; E60; 330; Pension Systems; Social Security; Risk sharing; Portfolio Choice; Relative Consumption